Vocabulary Competency and Reading Comprehension of Grade 12 English as Second Language Users: A Systematic Review - Chipili, Denson; Mwansa, Dickson M.; Mpolomoka, Daniel L. (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
This paper has three main objectives: (1) establish the relationship between performance in vocabulary with performance in reading comprehension and writing; (2) determine whether good performance in reading comprehension automatically translates into corresponding good performance in vocabulary and writing or not; (3) establish the correlation between gender and performance in vocabulary, reading comprehension and writing attainment among Grade 12 students. Numerous first language studies show a high correlation between good readers and writers, assuming reading and writing mutually reinforce each other. Some explore the link between vocabulary size and depth and their correlation with reading and writing. Fewer studies examined the connection of (1) vocabulary and reading comprehension and (2) vocabulary knowledge and writing in a second language environment. These studies have reported that second language inputs (reading and writing) play a pivotal role in developing literacy skills amongst learners in second language contexts, i.e., reading input affects the development of writing and reading abilities and or vice versa (meaning, writing input could have the same effect). We recommend that education standards officers, school administrators, and teachers should design strategies to develop in students the habit of independent reading.